PERUBAHAN SOSIAL MASYARAKAT GAMPONG GUNONG MEULINTEUNG DARI PETANI MENJADI PEKEBUN SAWIT - Aminah Aminah; Effendi Hasan (Jurnal Community, 2017)
This study aims to explain the factors that lead to social change in the village society farmer Gunong Meulinteung Panga District of Aceh Jaya district. The method used in this research is qualitative method. The data in this research was obtained through literature (library research) and field research. The research literature is done by reading text books, while research conducted field research by interviewing informants. The results showed that in the process of social change Gampong Gunong Meulinteung Panga District of Aceh Jaya district, there has been a shift in community work Gampong Gunong Meulinteung to earn income and income from the local economy who previously worked as a rice farmer turned into oil palm planters community. Social change in this community work caused by several factors: internal factors that consist of Population changes, new invention, lack of facilities.External factors consist of no irrigation factors, factors of rice pests, natural factors, the influence of other people. Keywords: Social Change, Farmers Rice and Oil Palm Plantations